Effects of vitamin E and vitamin A supplementation on performance, thyroid status and serum concentrations of some metabolites and minerals in broilers reared under heat stress (32°C) - Şahin, Nurhan; Şahin, Kazım; Küçük, Ömer (Czech Academy Agricultural Sciences, 2001)
An experiment on Cobb-500 male broilers was conducted to evaluate the effects of vitamin E (alpha-tocopherolacetate), vitamin A (retinol), and their combination on broiler performance and serum concentrations of triiodothyronine (T-3), thyroxine (T-4), adrenocorticotropine hormone (ACTH) and some metabolite and mineral concentrations in broilers reared under heat stress (32degreesC). One day-old 120 broilers were randomly assigned to 4 treatment groups, 3 replications of 10 birds each. The birds were fed either a control diet or a control diet supplemented with either vitamin A (15 000 IU retinol/kg diet), vitamin E (250 mg alpha-tocopherol-acetate/kg diet), or a combination of vitamin A and E (15 000 IU retinol plus 250 mg of alpha-tocopherolacetate/kg diet). Considered separately or as a combination, supplemental vitamin A and vitamin E increased feed intake (P = 0.01) and live weight gain (P = 0.03). However, feed efficiency remained similar in all treatments (P = 0.18). Serum T-3 and T-4 concentrations were also higher (P less than or equal to 0.001) with vitamin A, vitamin E, and vitamin A plus vitamin E groups than those of the control. However, ACTH concentration in serum was lower (P less than or equal to 0.001) in supplemental dietary vitamin groups compared with control. Serum glucose, uric acid, triglyceride, and cholesterol concentrations decreased (P:5 0,001) while protein and albumin concentrations increased (P less than or equal to 0.001) when both dietary vitamin E and vitamin A were supplemented. Serum activities of serum glutamic oxalate transaminase (SGOT) and serum glutamic pyruvate transaminase (SGPT) were not influenced by dietary vitamin E, vitamin A nor by a combination of vitamin A and vitamin E (P > 0.72). However, serum activity of alkaline phosphatase (AP) increased (P less than or equal to 0.001) with supplemental dietary vitamin E, vitamin A, or a combination of vitamin A and vitamin E. In addition, supplemental dietary vitamin E and vitamin A resulted in an increase in serum concentrations of both Ca and P (P less than or equal to 0.001), In general, when a significant effect was found for a parameter, the magnitude of responses to vitamin supplements was greatest with the combination of vitamin A and vitamin E, rather than that of each vitamin supplement separately. The results of the present study show that supplementing a combination of dietary vitamin E and vitamin A offers a good management practice to reduce heat stress-related decreases in broiler performance.
Keywords: heat stress; vitamin E; vitamin A; broilers; performance; blood parameters